2020
DOI: 10.1016/j.physio.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracoscopic lobectomy: which patients require postoperative physiotherapy?

Abstract: Objectives: Following major thoracic surgery physiotherapy is recommended to improve reduced lung volume, aid secretion clearance, and improve mobility, however, in many centres physiotherapy provision is variable following minimally invasive Video-Assisted Thoracoscopic Surgery (VATS). The objective of this study was to observe frequency of pulmonary disease (COPD), body mass index (BMI), preoperative mobility and age were independently associated with issues potentially amenable to physiotherapy (p=0.013). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Although the invasion was minimal after VATS, we have thought that the physical function and walking ability of the patients decreased after VATS because their physical activity decreased due to pain and thoracic drain placement. As with postoperative patients with other diseases, the importance of an early increase in physical activity has been shown from the study with VATS patients [7]. This study has confirmed the previous study, and we, therefore, consider the importance of early rehabilitation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although the invasion was minimal after VATS, we have thought that the physical function and walking ability of the patients decreased after VATS because their physical activity decreased due to pain and thoracic drain placement. As with postoperative patients with other diseases, the importance of an early increase in physical activity has been shown from the study with VATS patients [7]. This study has confirmed the previous study, and we, therefore, consider the importance of early rehabilitation.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding rehabilitation for VATS patients, enhanced recovery program including rehabilitation has been shown to have no effect on cardiopulmonary complications, 30-and 90-day mortality, length of stay, and readmissions [6]. On the other hand, other studies have shown that most of VATS lobectomy patients demonstrated conditions potentially amenable to rehabilitation [7]. Therefore, it has been reported that all patients need to receive routine postoperative rehabilitation evaluations to identify problems early and correctly [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for many anesthesiologists and thoracic surgeons, postoperative pain management, especially early postoperative pain, remains a source of concern [ 3 ]. Postoperative pain after VATLS might result in several pulmonary complications, such as atelectasis and hypercapnia, as well as lung infection, which can affect the quality of recovery(QoR) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, most patients experience a variety of complications, such as bleeding, infections, postoperative pain and early postoperative cognitive dysfunction (EPPNCD). [ 11 14 ] Thus, it is very important to choose an effective analgesia with fewer complications, especially for EPPNCD.…”
Section: Introductionmentioning
confidence: 99%